Description of Altruistic Behavior of Muhammadiyah Volunteers in Spreading Covid-19 in Sidoarjo - Ratih Puspita Anggraenni; Hazim Hazim (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to find out the description of altruistic behavior in MDMC volunteers in the screening of COVID-19 corpses in Sidoarjo and to find out what factors encourage their involvement as MDMC volunteers in the screening of COVID-19 corpses in Sidoarjo. The method used is qualitative in the form of phenomenology. This study also uses an interview technique based on Story Telling and semi-structured interviews. The subject of the study was an MDMC volunteer in Sidoarjo who served as the relocation of COVID-19 bodies in Sidoarjo. The results of this study are that the subject can take the time to help others who are in need, in addition to taking the time the subject also feels tolerant when he sees a corpse that has died from Covid-19, not only that the five research subjects also have a high social spirit, they can control themselves, and they also basically have a helping spirit from an early age which is obtained from parenting patterns from childhood.